STRATEGI PENINGKATAN PENGELOLAAN ASET DESA DI KABUPATEN MAJALENGKA - Bani Fadilah Ranandar; Otong Karyono (DIALOGIKA, 2020)
Obstacles in reporting village assets because asset officers are less disciplined in collecting inventory data, so that the local government has not been able to conduct village asset appraisals. Supervision of the implementation of village asset management that should have been carried out by the Regional Government or the District Government has never been carried out. From the results of the analysis of the SWOT analysis strategy formulation strategy to increase village assets, it is found that the SWOT analysis quadrant is in quadrant II, namely the diversification strategy. This analysis has a number of strengths but there are several threats. The results of the analysis show that the current threat exists in the impact of the Covid 19 pandemic which has changed most of the development programs towards village assets in order to increase village income into social / assistance programs intended for highly affected communities. Even though the program comes from local, provincial and central governments, the involvement of assistance from the village itself is very strategic considering that assistance from local, provincial and central governments is relatively limited